Pengaruh Zakat Perbankan dan Corporate Social Responsibility terhadap Rasio Profitabilitas Bank Umum Syariah - Indah Nur Ainun; Nofinawati N; Windari W (Journal of Islamic Social Finance Management, 2021)
ABSTRACTBased on data obtained from Islamic Commercial Banks in Indonesia as many as 9 banks the percentage of Banking Zakat, Corporate Social Responsibility and Return On Assets fluctuated, but the increase that occurred in Banking Zakat and Corporate Social Responsibility was not always followed by an increase in Return On Assets. This study aims to determine the effect of banking zakat and corporate social responsibility on the profitability ratios of Islamic Commercial Banks in Indonesia 2013-2018 either partially or simultaneously. This research is a quantitative research, the data source comes from secondary data in the form of pooled data. The results showed that partially banking zakat had a significant effect on return on assets of Islamic Commercial Banks in Indonesia, partially corporate social responsibility had no significant effect on return on assets of Islamic Commercial Banks in Indonesia. Meanwhile, simultaneously banking zakat and corporate social responsibility have a significant influence on the return on assets of Islamic Commercial Banks in Indonesia. Keywords : Banking Zakat, Corporate Social Responsibility, Return On Asset ABSTRAK Berdasarkan data yang diperoleh dari Bank Umum Syariah di Indonesia sebanyak 9 bank persentase Zakat Perbankan, Corporate Social Responsibility dan Return On Asset mengalami fluktuasi, namun kenaikan yang terjadi pada Zakat Perbankan dan  Corporate Social Responsibility tidak selalu diikuti dengan kenaikan Return On Asset. Penelitian ini bertujuan untuk mengetahui pengaruh zakat perbankan dan corporate social responsibility terhadap rasio profitabilitas Bank Umum Syariah di Indonesia 2013-2018 baik secara parsial maupun secara simultan. Penelitian ini adalah penelitian kuantitatif, sumber data berasal dari data sekunder dengan bentuk pooled data. Hasil penelitian menunjukkan secara parsial zakat perbankan berpengaruh signifikan terhadap return on asset Bank Umum Syariah di Indonesia, corporate social responsibility secara parsial tidak berpengaruh signifikan terhadap return on asset Bank Umum Syariah di Indonesia.  Sedangkan secara simultan zakat perbankan dan corporate social responsibility memiliki pengaruh yang signifikan terhadap return on asset Bank Umum Syariah di Indonesia. Kata Kunci   : Zakat Perbankan, Corporate Social Responsibility, Return On Asset